Moderating Competitive Advantage On Factors Affecting MSMEs Business Performance In The Time Of Covid-19 - Bekti Karnowati, Nandang; Najmudin, Najmudin; Suwandari, Lusi; Adi Prakoso, Fajar; Widya Apriandi, Devy (International Journal of Science, Technology & Management, 2023)
This study aims to investigate how MSMEs in Cilacap capacity to compete and perfome well in the marketing arena are impected by market orientation and entrepreneurial orientation. The goal of this study is to balance the effect of market orientation on bussiness performance by looking at the potential moderating function of competitive advantage. Partial Least Square model analysis is used in the study. MSMEs business actors werw given a quetionnaire with a likert scale and five possible answers. We discovered that whilw market orientation is crucial for creating a competittive edge, it has no real bearing on how well a company performs. Additionally, whereas entrepreneurial mindset direccty affects corporate performance, it has little impact on competitive advantage. MSME business actors need to able to create fresh concept that can help the neighborhood deal with socioeconomic issue brought on by the Covid-19 pndemic.